Elementos autoritários em Carl Schmitt: breve estudo dos escritos de Weimar (1919-1932) - Garzillo, Rômulo Monteiro (2020)
The object of this dissertation is the authoritarian content of the texts written by the German constitutionalist, Carl Schmitt, between the years of 1919 and 1932, a period known as the Weimar Republic. Its general objective is to understand the structure of authoritarianism, as an idea and political movement. Its specific objectives are to analyze, identify and systematize the authoritarian elements of his work. The research justification is the importance of understanding the elements that compose the authoritarian phenomenon, and additionally the better understanding of the nature, origin, history and objectives of the constitutional democratic regimes. The choice for Carl Schmitt's work results from the author's own biography, which was one of the most relevant constitutionalists of his time and defender of the dictatorship and the state of exception. Furthermore, Carl Schmitt's ideas were not limited to academic debate, but they were able to seduce politicians linked to National Socialism, culminating in the author's effective participation in the totalitarian regime led by Adolf Hitler. The adopted method establishes a comparison between Carl Schmitt's main ideas and the founding elements of constitutional democracy. Throughout this dissertation, it appears that the ideas developed by Carl Schmitt are opposed to the values of modernity, illuminism and liberalism, both in the legal and political sense. The denial consequence of the Rule of Law under liberal molds puts Carl Schmitt in confrontation with the Austrian positivist Hans Kelsen, which ends up generating one of the greatest legal debates of the 20th century. In this clash, it appears that the Schmitt's work is organized through a triad of elements – cultural, legal and political – that end up denying the whole ideas framework prepared by the liberal movement called constitutionalism